A preparation method of a power battery shell and its application
The extrusion mold is processed through alloy composition design and three-stage nitriding process, which solves the problem of low yield of thin-walled shell of the power battery shell, realizes high-precision dimensional control and appearance optimization, and significantly improves the yield rate.
Patent Information
- Application Number
- CN202211648518.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-12-21
AI Technical Summary
In the prior art, it is difficult to prepare thin-walled power battery shells with excellent performance, especially in square battery shells with equal or unequal walls. There are problems such as unstable size of the pulling blank and prone to feel scratches and burrs, resulting in low yield.
Through the alloy composition design and control of the extrusion process, precise control of the size of the extruded product and optimization of the appearance are achieved. The extrusion mold is processed by a three-stage nitriding process to improve the depth and hardness of the nitriding diffusion layer of the mold, thereby ensuring the normal progress of the drawing process.
The high-precision dimensional control and appearance optimization of the power battery case are achieved, and the yield rate of the pulling section is improved. The yield rate is increased by about 33 to 54% when semi-continuous extrusion is 1500 meters.
Smart Images

Figure BDA0004010885490000071 
Figure BDA0004010885490000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metallurgical materials, and specifically relates to a preparation method of a power battery shell and application thereof. Background Art
[0002] Thinning the wall of aluminum alloy power battery shell is an important way to achieve weight reduction, improve space utilization and charge capacity. Based on the needs of the use scenario, it is required to have good corrosion resistance, excellent thermal conductivity and laser weldability. The material is 3003 and it needs to have certain strength and hardness. The outer circle diameter is more than 100mm, the aspect ratio is 2-5, and the thinnest wall thickness of the battery shell with equal or unequal walls is 0.3mm. The wall thickness accuracy requirement is ±0.08 or even more stringent.
[0003] There are several types of aluminum alloy power battery shells (round or square) made by existing manufacturing technology: the first is to use 3003 material or improved alloy, roll it into thin plates, cut it and then deep-draw it; the second is to use 3003 material or improved alloy, extrude it into plates, cut it and then reverse-extrude it; the third is to use 3003 material or improved alloy, and cold-draw the hot extruded blank. The first and second methods are limited in length because the friction force of deep drawing or reverse extrusion and the difficulty of demolding increase significantly with the increase of length, and the maximum length cannot exceed 500mm; the length of the finished product of the third method is not limited. The existing technology has advantages in making round battery shells with equal walls. The reason is that the blank for drawing (i.e., the extruded product) is round. According to the principle of concentric circles in the center of the extrusion die, the extrusion difficulty is low. At the same time, the extruded blank is round, the drawing is round, and the deformation amount is consistent everywhere. The drawing fracture and wrinkling of the drawn product caused by inconsistent deformation and asynchronism are almost non-existent. When used to make battery shells with equal walls on four sides, it can be achieved when the thickness of the four sides is above 0.7mm. It is difficult to achieve when used to make square battery shells with equal walls or unequal walls (and the minimum wall thickness is less than 0.7mm). The main problems are Including: 1) The size of the drawn billet (i.e. the finished product of hot extrusion) is extremely unstable. As we all know, during the hot extrusion process, due to the influence of the temperature fluctuation of the cast rod and the friction temperature rise of the extrusion die during the extrusion process, the size of the extruded product in the same cross section will change, and the head and tail of the extruded product will also change, and there is no regularity. When the wall thickness of the cold-drawn product is relatively small (wall thickness <0.7mm), the corresponding wall thickness of the drawn billet should also be reduced synchronously. At this time, the relative deviation of the wall thickness change of the drawn billet is large, resulting in a large difference in the degree of drawing deformation at various locations. Waves, wrinkles, and even breakage often appear at the wall thickness difference, making drawing impossible. 2) The drawn billet (i.e. the finished product of hot extrusion) is very prone to hand scratches and burrs. As the extrusion proceeds, the defects become more and more obvious. When the defects reach a certain depth, it affects the dimensional accuracy of the extruded profile. The defects form a notch effect in the subsequent drawing process, resulting in breakage and cracking, affecting the efficiency and yield rate. The defects have a particularly obvious impact on thin-walled battery shells.Chinese patent CN110983115A discloses an improved 3003 aluminum alloy strip and a preparation method thereof. The patented technology controls the aluminum alloy composition to Si 0.5-0.7%, Fe 0.6-0.8%, Cu 0.05-0.2%, Mn 1.0-1.5%, Mg0-0.02%, Zn 0-0.02%, and Mg+Zn<0.03%, the rest is Al, and inevitable impurities, and a strip with a thickness of 1.8-3.5 mm is obtained through the steps of melting, ingot homogenization, hot rolling, cold rolling, stretching, bending, straightening and cutting. Therefore, this technical solution cannot produce a thin-walled battery shell with excellent performance in the process of preparing a power battery shell; Chinese patent CN112662915A discloses an aluminum alloy and a preparation method and application thereof. The patented technology uses an aluminum alloy material with a specific metal content, controls the Mn and Fe contents, and improves the performance of the battery shell. In one step, a three-stage homogenization treatment and a cold drawing (deformation of 15-30%) are used to obtain a thin-walled square battery shell with a maximum wall thickness of 0.4-0.55mm and a circumscribed circle diameter of 138.5-140mm. However, this patented technical solution contains a certain amount of Mg / Zr / Cr elements, and has a large resistance to extrusion deformation. It is suitable for preparing battery shells with thicker walls (the thinnest wall thickness of the extruded material is 0.5mm, and the thinnest wall thickness of the finished product is 0.4mm). At the same time, due to a certain amount of Mg element, the melting point is low and it is easy to volatilize during the welding process, which is easy to form defects such as welding pores.
[0004] In summary, the preparation of a thin-walled (equal-walled or unequal-walled) battery casing with excellent performance is not yet achievable with the existing technology. Therefore, it is of great significance to develop an aluminum alloy and a preparation process for preparing a power battery casing with equal or unequal walls. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention realizes precise control of the size and appearance of the extruded product (drawing blank) by designing the alloy composition and controlling the extrusion process. By implementing a three-stage nitriding process on the extrusion die, the depth and hardness of the nitrided diffusion layer in the working zone of the extrusion die are improved, thereby ensuring the appearance of the semi-finished product of the extrusion section and achieving high-precision dimensional control, thereby ensuring the normal progress of the drawing process.
[0006] In a first aspect, the present invention provides a method for preparing a power battery shell, comprising the following steps:
[0007] S1, mixing metal materials, melting and casting to obtain an aluminum alloy ingot A;
[0008] S2, homogenizing the aluminum alloy ingot A to obtain an aluminum alloy ingot B;
[0009] S3, heating and extruding the aluminum alloy ingot B, and subjecting the extrusion die to a three-stage nitriding process before extrusion: keeping the temperature in a salt bath at 490-510°C for 2 hours for primary nitriding treatment, then heating to 510-530°C for 2 hours for secondary nitriding treatment, and finally cooling to 480-500°C for 4 hours for tertiary nitriding treatment; the secondary nitriding temperature is 15-25°C higher than the primary nitriding temperature, and the tertiary nitriding temperature is 25-35°C lower than the secondary nitriding temperature, and extruding to obtain aluminum alloy C;
[0010] S4. Drawing the aluminum alloy C to prepare a power battery shell.
[0011] Furthermore, in terms of mass percentage, the metal material composition in step S1 of the power battery shell preparation method is: Cu 0.09-0.20%, Fe≤0.70%, Mn 1.00-1.20%, Si≤0.60%, Mg+Zn+Li≤0.05, Ti≤0.03%, and the remainder is Al and unavoidable impurities.
[0012] Furthermore, the metal material includes inevitable impurities whose individual content is ≤0.05% and whose total content is ≤0.15% by mass percentage.
[0013] Furthermore, in the melting and casting in step S1 of the power battery shell preparation method, an online box degassing device and a ceramic filter plate in series with a tubular filter are used to treat the melt purity, and the hydrogen content is ≤0.12ml / 100gAl.
[0014] Furthermore, in step S2 of the power battery shell preparation method, the homogenization conditions are as follows: heating to 600°C within 0.5h, heating from 600°C to 620°C within 1.5-2.5h, keeping warm for 8-12h, and then cooling to room temperature by wind and mist, keeping warm for 10h, and then cooling to room temperature by wind and mist.
[0015] Furthermore, in step S3 of the power battery shell preparation method, the extrusion process is as follows: the temperature of the aluminum alloy ingot B is controlled at 460-510° C., and the extrusion rod advancement speed is 2-5 mm / s.
[0016] Furthermore, the salt bath in step S3 is composed of: nitrogen is introduced into sodium hydroxide, CNO - The mass concentration was controlled at 38% ± 5%.
[0017] In a second aspect, the present invention provides a power battery case.
[0018] Further, the shell is designed to have equal walls or unequal walls;
[0019] Furthermore, the ratio of the length to width of the shell is 2 to 5:1, and the wall thickness is ≥0.3 mm.
[0020] In a third aspect, the present invention further provides a three-stage nitriding process for an aluminum alloy extrusion die, the three-stage nitriding process comprising the following steps:
[0021] The mold is kept in a salt bath at 490-510°C for 2 hours for primary nitriding treatment, then heated to 510-530°C for 2 hours for secondary nitriding treatment, and finally cooled to 480-500°C for 4 hours for tertiary nitriding treatment. The secondary nitriding temperature is 15-25°C higher than the primary nitriding temperature, and the tertiary nitriding temperature is 25-35°C lower than the secondary nitriding temperature.
[0022] Furthermore, in the step, the salt bath is composed of sodium hydroxide, nitrogen is introduced, and CNO - The mass concentration was controlled at 38% ± 5%.
[0023] In a third aspect, the present invention also provides applications of the power battery housing in the fields of capacitor electrical, new energy, etc.
[0024] Since the battery shell uses 3 series aluminum-manganese alloy, it contains AlMnFe and MnAl with high hardness. 6 The second phase, AlMnFe, has a microhardness of about 700 HV, MnAl 6 The microhardness is about 540HV. These hard second phase particles rub violently with the mold working belt. When the surface hardness of the mold working belt is soft, these hard particles may be embedded or adhered to the mold working belt, causing white spots when the aluminum alloy flows through the working belt. In severe cases, dents and scratches will appear. The dents and scratches on the appearance of the extruded profiles form a notch effect, which also affects the deformation at this position during the drawing process, resulting in drawing fractures or cracks. Therefore, the present invention improves the performance of the aluminum alloy in the extrusion process by improving the aluminum alloy composition and the preparation process conditions, and prepares a power battery shell with excellent performance.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The extrusion die obtained by the tri-nitriding process used in the preparation process of the power battery shell of the present invention has a thicker nitrided diffusion layer (above 125μm) and a high surface microhardness (above 1240HV). It can achieve a clear appearance of the extruded profile without scratches or depressions when the extrusion discharge is 1500 meters, effectively ensuring the efficiency and yield of the drawing section (84-86%). Compared with the prior art, the preparation method of the present invention increases the yield of the power battery shell in the drawing section by about 1-22% when the semi-continuous extrusion is 300 meters, and increases the yield of the drawing section by about 33-54% when the semi-continuous extrusion is 1500 meters. DETAILED DESCRIPTION
[0027] The experimental methods in the following examples of the present invention, where no specific conditions are specified, are usually carried out under conventional conditions or under conditions recommended by the manufacturers. The various commonly used chemical reagents used in the examples are all commercially available products.
[0028] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0029] The terms "including" and "having" and any variations thereof of the present invention are intended to cover non-exclusive inclusions. For example, a process, method, device, product or equipment comprising a series of steps is not limited to the listed steps or modules, but may optionally include steps not listed, or may optionally include other steps inherent to these processes, methods, products or equipment.
[0030] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0031] The present invention is further described in the following examples, but the examples are not intended to limit the scope of protection of the present invention.
[0032] Example 1
[0033] The method for preparing the power battery shell of this embodiment includes the following steps:
[0034] S1. Mix the metal materials according to the mass percentage, melt and cast the metal materials, and use an online box degassing device and a ceramic filter plate in series with a tubular filter to treat the melt purity, so as to obtain an aluminum alloy ingot A with a hydrogen content of 0.12 ml / 100 gAl, and the ingot composition is Cu 0.15%, Fe 0.40%, Mn 1.12%, Si 0.09%, Mg+Zn+Li: 0.05%, Ti 0.02%, and the balance is Al and inevitable impurities (the individual content of inevitable impurities is ≤0.05%, and the total amount is ≤0.15%);
[0035] S2, homogenizing the aluminum alloy ingot A to obtain an aluminum alloy ingot B, the homogenization conditions are: heating to 600°C for 0.5h, heating from 600°C to 620°C for 2h, keeping the temperature for 10h, and then cooling to room temperature by wind and mist;
[0036] S3, the aluminum alloy ingot B is heated and extruded. During the extrusion process, the ingot temperature is controlled at 465±5℃, the extrusion rod advances at a speed of 4.2mm / s, and the extrusion die is subjected to a three-stage nitriding process before extrusion: the first stage nitriding treatment is carried out in a 500℃ salt bath for 2h, then the temperature is raised to 520℃ for 2h for the second stage nitriding treatment, and finally the temperature is lowered to 490℃ for 4h for the third stage nitriding treatment. The second stage nitriding temperature is 20℃ higher than the first stage nitriding temperature, and the third stage nitriding temperature is 30℃ lower than the second stage nitriding temperature. CNO in the salt bath - % concentration 38%, aluminum alloy C is obtained by extrusion;
[0037] S4. Aluminum alloy C is drawn, and the drawing deformation at the center of the long side and the short side is 15%, and the deformation at both sides of the long side and the short side is 13%, to prepare a square power battery shell with a long side of 100 mm, a wide side of 30 mm, a thin side wall thickness of 0.3 mm, and a thick side wall thickness of 1.2 mm.
[0038] Example 2
[0039] The method for preparing the power battery shell of this embodiment includes the following steps:
[0040] S1. Mix the metal materials according to the mass percentage, melt and cast the metal materials, and use an online box degassing device and a ceramic filter plate in series with a tubular filter to treat the melt purity, so as to obtain an aluminum alloy ingot A with a hydrogen content of 0.12 ml / 100 gAl, and the ingot composition is Cu 0.15%, Fe 0.40%, Mn 1.12%, Si 0.09%, Mg+Zn+Li: 0.05%, Ti 0.02%, and the balance is Al and inevitable impurities (the individual content of inevitable impurities is ≤0.05%, and the total amount is ≤0.15%);
[0041] S2, homogenizing the aluminum alloy ingot A to obtain an aluminum alloy ingot B, the homogenization conditions are: heating to 600°C for 0.5h, heating from 600°C to 620°C for 2h, keeping the temperature for 10h, and then cooling to room temperature by wind and mist;
[0042] S3. The aluminum alloy ingot B is heated and extruded. During the extrusion process, the ingot temperature is controlled at 465±5℃, the extrusion rod advances at a speed of 4.2mm / s, and the extrusion die is subjected to a three-stage nitriding process before extrusion: the first stage nitriding treatment is carried out in a 490℃ salt bath for 2h, then the temperature is raised to 515℃ for 2h for the second stage nitriding treatment, and finally the temperature is lowered to 490℃ for 4h for the third stage nitriding treatment. The second stage nitriding temperature is 25℃ higher than the first stage nitriding temperature, and the third stage nitriding temperature is 25℃ lower than the second stage nitriding temperature. The CNO - % concentration 38%, aluminum alloy C is obtained by extrusion;
[0043] S4. Aluminum alloy C is drawn, and the drawing deformation at the center of the long side and the short side is 15%, and the deformation at both sides of the long side and the short side is 13%, to prepare a square power battery shell with a long side of 150 mm, a wide side of 50 mm, a thin side wall thickness of 0.35 mm, and a thick side wall thickness of 1.7 mm.
[0044] Example 3
[0045] The method for preparing the power battery shell of this embodiment includes the following steps:
[0046] S1. Mix the metal materials according to the mass percentage, melt and cast the metal materials, and use an online box degassing device and a ceramic filter plate in series with a tubular filter to treat the melt purity, so as to obtain an aluminum alloy ingot A with a hydrogen content of 0.12 ml / 100 gAl, and the ingot composition is Cu 0.17%, Fe 0.42%, Mn 1.14%, Si 0.12%, Mg+Zn+Li: 0.05%, Ti 0.015%, and the balance is Al and inevitable impurities (the individual content of inevitable impurities is ≤0.05%, and the total amount is ≤0.15%);
[0047] S2, homogenizing the aluminum alloy ingot A to obtain an aluminum alloy ingot B, the homogenization conditions are: heating to 600°C for 0.5h, heating from 600°C to 620°C for 2h, keeping the temperature for 10h, and then cooling to room temperature by wind and mist;
[0048] S3, the aluminum alloy ingot B is heated and extruded. During the extrusion process, the ingot temperature is controlled at 465±5℃, the extrusion rod advances at a speed of 4.2mm / s, and the extrusion die is subjected to a three-stage nitriding process before extrusion: the first stage nitriding treatment is carried out in a 505℃ salt bath for 2h, then the temperature is raised to 520℃ for 2h for the second stage nitriding treatment, and finally the temperature is lowered to 495℃ for 4h for the third stage nitriding treatment. The second stage nitriding temperature is 20℃ higher than the first stage nitriding temperature, and the third stage nitriding temperature is 25℃ lower than the second stage nitriding temperature. The CNO - % concentration 38%, aluminum alloy C is obtained by extrusion;
[0049] S4. Aluminum alloy C is drawn, and the drawing deformation at the center of the long side and the short side is 15%, and the deformation at both sides of the long side and the short side is 13%, to prepare a square power battery shell with a long side of 150 mm, a wide side of 25 mm, a thin side wall thickness of 0.3 mm, and a thick side wall thickness of 1.2 mm.
[0050] Example 4
[0051] The method for preparing the power battery shell of this embodiment includes the following steps:
[0052] S1. Mix the metal materials according to the mass percentage, melt and cast the metal materials, and use an online box degassing device and a ceramic filter plate in series with a tubular filter to treat the melt purity, so as to obtain an aluminum alloy ingot A with a hydrogen content of 0.12 ml / 100 gAl, and the ingot composition is Cu 0.15%, Fe 0.40%, Mn 1.12%, Si 0.09%, Mg+Zn+Li: 0.05%, Ti 0.02%, and the balance is Al and inevitable impurities (the individual content of inevitable impurities is ≤0.05%, and the total amount is ≤0.15%);
[0053] S2, homogenizing the aluminum alloy ingot A to obtain an aluminum alloy ingot B, wherein the homogenization conditions are: heating to 600° C. within 0.5 h, heating from 600° C. to 620° C. within 1.5 h, keeping the temperature for 8 h, and then cooling to room temperature by wind and mist;
[0054] S3, the aluminum alloy ingot B is heated and extruded. During the extrusion process, the ingot temperature is controlled at 465±5℃, the extrusion rod advances at a speed of 4.2mm / s, and the extrusion die is subjected to a three-stage nitriding process before extrusion: the first stage nitriding treatment is carried out in a 500℃ salt bath for 2h, then the temperature is raised to 520℃ for 2h for the second stage nitriding treatment, and finally the temperature is lowered to 490℃ for 4h for the third stage nitriding treatment. The second stage nitriding temperature is 20℃ higher than the first stage nitriding temperature, and the third stage nitriding temperature is 30℃ lower than the second stage nitriding temperature. CNO in the salt bath - % concentration 38%, aluminum alloy C is obtained by extrusion;
[0055] S4. Aluminum alloy C is drawn, and the drawing deformation at the center of the long side and the short side is 15%, and the deformation at both sides of the long side and the short side is 13%, to prepare a square power battery shell with a long side of 100 mm, a wide side of 30 mm, a thin side wall thickness of 0.3 mm, and a thick side wall thickness of 1.2 mm.
[0056] Example 5
[0057] The method for preparing the power battery shell of this embodiment includes the following steps:
[0058] S1. Mix the metal materials according to the mass percentage, melt and cast the metal materials, and use an online box degassing device and a ceramic filter plate in series with a tubular filter to treat the melt purity, so as to obtain an aluminum alloy ingot A with a hydrogen content of 0.12 ml / 100 gAl, and the ingot composition is Cu 0.13%, Fe 0.38%, Mn 1.06%, Si 0.10%, Mg+Zn+Li: 0.05%, Ti 0.015%, and the balance is Al and inevitable impurities (the individual content of inevitable impurities is ≤0.05%, and the total amount is ≤0.15%);
[0059] S2, homogenizing the aluminum alloy ingot A to obtain an aluminum alloy ingot B, wherein the homogenization conditions are: heating to 600° C. within 0.5 h, heating from 600° C. to 620° C. within 1.5 h, keeping the temperature for 8 h, and then cooling to room temperature by wind and mist;
[0060] S3, the aluminum alloy ingot B is heated and extruded. During the extrusion process, the ingot temperature is controlled at 465±5℃, the extrusion rod advances at a speed of 4.2mm / s, and the extrusion die is subjected to a three-stage nitriding process before extrusion: the first stage nitriding treatment is carried out in a 508℃ salt bath for 2h, then the temperature is raised to 525℃ for 2h for the second stage nitriding treatment, and finally the temperature is lowered to 490℃ for 4h for the third stage nitriding treatment. The second stage nitriding temperature is 17℃ higher than the first stage nitriding temperature, and the third stage nitriding temperature is 35℃ lower than the second stage nitriding temperature. CNO in the salt bath - % concentration 38%, aluminum alloy C is obtained by extrusion;
[0061] S4. Aluminum alloy C is drawn, and the drawing deformation at the center of the long side and the short side is 15%, and the deformation at both sides of the long side and the short side is 13%, to prepare a square power battery shell with a long side of 100 mm, a wide side of 30 mm, a thin side wall thickness of 0.3 mm, and a thick side wall thickness of 1.2 mm.
[0062] Test Example 1: Performance Test
[0063] According to GB / T 4340.1-2009 "Metallic Materials Vickers Hardness Test Part 1", the hardness of the extrusion dies after nitriding of the embodiment and the comparative example was tested using a digital Vickers hardness tester. The test results are shown in Table 1.
[0064] According to GB / T 11354-2005 "Determination of nitriding layer depth and metallographic structure inspection of steel parts", the nitriding layer of the embodiment and the comparative example was measured using a metallographic microscope. The test results are shown in Table 1.
[0065] According to GB / T 6892-2006 "Aluminum and aluminum alloy extruded profiles for general industrial use", visually observe the surface of the product, touch the surface with your fingertips, and measure the depth of the defect;
[0066] The yield rate of the drawing section is equal to the total qualified products after drawing into power battery shells divided by the total output of the extrusion section.
[0067] Table 1 Performance test results of power battery shells prepared in Examples 1 to 5
[0068]
[0069] It can be seen from the results in Table 1 that the surface microhardness of the nitrided diffusion layer of the extrusion die in the preparation process of the power battery shell of the present invention can reach 1240-1257 HV, the depth of the nitrided layer can reach 125-135 μm, the semi-finished product obtained in the extrusion section has a clear appearance, no scratches or depressions, and the yield of the power battery shell in the drawing section can reach 84-86%. The test results show that the power battery shell prepared by the preparation method of the present invention has excellent performance.
[0070] Comparative Example 1
[0071] The difference from Example 4 is that the three-stage nitriding process in step S3 is: the first stage nitriding treatment is carried out in a 490°C salt bath for 2 hours, then the temperature is raised to 520°C for 2 hours for the second stage nitriding treatment, and finally the temperature is lowered to 510°C for 4 hours for the third stage nitriding treatment. The second stage nitriding temperature is 30°C higher than the first stage nitriding temperature, and the third stage nitriding temperature is 10°C lower than the second stage nitriding temperature. The CNO - %concentration 38%.
[0072] Comparative Example 2
[0073] The difference from Example 4 is that the three-stage nitriding process in step S3 is: the first stage nitriding treatment is carried out in a 520°C salt bath for 2 hours, then the temperature is raised to 540°C for 2 hours for the second stage nitriding treatment, and finally the temperature is raised to 560°C for 4 hours for the third stage nitriding treatment. The second stage nitriding temperature is 20°C higher than the first stage nitriding temperature, and the third stage nitriding temperature is 20°C higher than the second stage nitriding temperature. The CNO - %concentration 38%.
[0074] Comparative Example 3
[0075] The difference from Example 4 is that the three-stage nitriding process in step S3 is: the first stage nitriding treatment is carried out in a 500°C salt bath for 4 hours, then the temperature is raised to 520°C for 4 hours for the second stage nitriding treatment, and finally the temperature is lowered to 490°C for 6 hours for the third stage nitriding treatment. The second stage nitriding temperature is 20°C higher than the first stage nitriding temperature, and the third stage nitriding temperature is 30°C lower than the second stage nitriding temperature. - %concentration 38%.
[0076] Comparative Example 4
[0077] The difference from Example 4 is that the three-stage nitriding process in step S3 is omitted.
[0078] Comparative Example 5
[0079] The difference from Example 4 is that the three-stage nitriding process in step S3 is replaced by a single-stage nitriding process, i.e., keeping in a 560° C. salt bath for 6 hours.
[0080] Comparative Example 6
[0081] The difference from Example 4 is that the three-stage nitriding process in step S3 is replaced by: keeping in a 520° C. salt bath for 2 hours, then heating to 560° C. and keeping for 4 hours.
[0082] Comparative Example 7
[0083] The difference from Example 4 is that the three-stage nitriding process in step S3 is: the first stage nitriding treatment is carried out in a 500°C salt bath for 2 hours, then the temperature is raised to 520°C for 2 hours for the second stage nitriding treatment, and finally the temperature is lowered to 490°C for 4 hours for the third stage nitriding treatment. The second stage nitriding temperature is 20°C higher than the first stage nitriding temperature, and the third stage nitriding temperature is 30°C lower than the second stage nitriding temperature. The CNO - %Concentration 30%.
[0084] Test Example 2: Performance Test
[0085] The performance of the power battery shells prepared in Comparative Examples 1 to 7 was measured according to the measurement method of Test Example 1. The measurement results are shown in Table 2.
[0086] Table 2 Performance test results of power battery shells prepared in Comparative Examples 1 to 7
[0087]
[0088] It can be seen from the results of Comparative Examples 1 to 7 in Table 2 that, compared with the power battery shell obtained by the preparation method of Examples 1 to 5, the nitriding process of the die in the extrusion process has a significant effect on the performance of the prepared power battery shell. Compared with Comparative Examples 1 to 7, the surface microhardness of the nitrided diffusion layer of the extrusion die obtained by the three-stage nitriding process of the die adopted in the technical solution of the present invention is significantly improved, and there is a deeper nitrided layer. The semi-finished product after semi-continuous extrusion of 1500m has a clear appearance, no scratches or depressions, and no dull, rough appearance, scratches and burrs, and defect depth. At the same time, the finished product rate of the power battery shell in the drawing section is increased by about 1-22% when the semi-continuous extrusion is 300 meters, and the finished product rate of the drawing section is increased by about 33-54% when the semi-continuous extrusion is 1500 meters. Therefore, it is shown that the performance of the power battery shell prepared by the preparation method of the present invention is significantly improved.
[0089] It should be noted that the specific features, structures, materials or characteristics described in this specification can be combined arbitrarily. In order to make the description concise, not all possible combinations of the various technical features in the above embodiments are described. If there is no contradiction, technicians in this field can combine and combine the different embodiments and features of different embodiments described in this specification.
[0090] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a power battery shell, characterized in that: The following steps are involved: S1, mixing metal materials, melting and casting to obtain an aluminum alloy ingot A; S2, homogenizing the aluminum alloy ingot A to obtain an aluminum alloy ingot B; S3, heating and extruding the aluminum alloy ingot B, and subjecting the extrusion die to a three-stage nitriding process before extrusion: keeping the temperature in a salt bath at 490-510°C for 2 hours for primary nitriding treatment, then heating to 510-530°C for 2 hours for secondary nitriding treatment, and finally cooling to 480-500°C for 4 hours for tertiary nitriding treatment; the secondary nitriding temperature is 15-25°C higher than the primary nitriding temperature, and the tertiary nitriding temperature is 25-35°C lower than the secondary nitriding temperature, and extruding to obtain aluminum alloy C; S4, drawing the aluminum alloy C to prepare a power battery shell; The salt bath composition in step S3 is as follows: nitrogen is introduced into sodium hydroxide, CNO - The mass concentration was controlled at 38% ± 5%.
2. The method for preparing a power battery shell according to claim 1, characterized in that: In terms of mass percentage, the metal material composition in step S1 is: Cu 0.05-0.18%, Fe≤0.70%, Mn 1.00-1.20%, Si≤0.60%, Mg+Zn+Li≤0.05, Ti≤0.05%, and the remainder is Al and unavoidable impurities.
3. The method for preparing a power battery shell according to claim 2, characterized in that: Calculated by mass percentage, the individual content of inevitable impurities in the metal material is ≤0.05%, and the total amount is ≤0.15%.
4. The method for preparing a power battery shell according to claim 1, characterized in that: The homogenization conditions in step S2 are: heating to 600° C. within 0.5 h, heating from 600° C. to 620° C. within 1.5 to 2.5 h, keeping warm for 8 to 12 h, then cooling to room temperature by wind and mist, keeping warm for 10 h, and then cooling to room temperature by wind and mist.
5. The method for preparing a power battery shell according to claim 1, characterized in that: In the extrusion process of step S3, the temperature of the aluminum alloy ingot B is controlled at 460-510° C., and the extrusion rod advances at a speed of 2-5 mm / s.
6. A power battery shell obtained by the preparation method according to any one of claims 1 to 5.
7. The power battery case according to claim 6, characterized in that: The shell is designed with equal walls or unequal walls.
8. The power battery shell according to claim 6, characterized in that: The ratio of the length to width of the shell is 2 to 5:1, and the wall thickness is ≥0.3 mm.
9. A three-stage nitriding process for aluminum alloy extrusion dies, characterized in that: The three-stage nitriding process comprises the following steps: The mold is kept in a salt bath at 490-510°C for 2 hours for primary nitriding treatment, then heated to 510-530°C for 2 hours for secondary nitriding treatment, and finally cooled to 480-500°C for 4 hours for tertiary nitriding treatment. The secondary nitriding temperature is 15-25°C higher than the primary nitriding temperature, and the tertiary nitriding temperature is 25-35°C lower than the secondary nitriding temperature. The salt bath composition is as follows: nitrogen is introduced into sodium hydroxide, CNO - The mass concentration was controlled at 38% ± 5%.
Citation Information
Patent Citations
Improved 3003 aluminum alloy strip material as well as preparation method and application thereof
CN110983115A
Nitriding treatment method for aluminum profile extrusion die
CN112144009A
Aluminum alloy and preparation method and application thereof
CN112662915A
Aluminum alloy battery shell plate and production method thereof
CN115305389A
Lithium ion secondary battery outer can
JP2012174532A